Effect of using the simultaneous electronic presentations strategy in teaching basic skills of basketball to second-grade intermediate students - Ali, Maitham Saadi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of this study was to identify the effect of using the simultaneous electronic presentations strategy in teaching basic skills of basketball to second-grade intermediate students. The present study had a parallel group, pre-post experimental design. In the present study the students of the Salah al-Din Intermediate School for the academic year 2020-2021 constituted the research community. A total of 75 students were present in the research community. Out of 75 students 16 students were selected as the participants for the study. The students falling within the age group of 13-14 years were recruited as the study participants, making up a percentage of 21.33 of the total number. Based on the results of the present study, the researcher concluded that the use of the simultaneous electronic presentations strategy created an interactive environment, which reflected positively on teaching basic skills of basketball to second-grade intermediate students.